2012
DOI: 10.1309/ajcptdqchiwh4ohm
|View full text |Cite
|
Sign up to set email alerts
|

Microcalcification Is an Important Factor in the Management of Breast Intraductal Papillomas Diagnosed on Core Biopsy

Abstract: The follow-up excision (FUE) results were analyzed from 370 cases diagnosed as intraductal papilloma on breast core needle biopsy (CNB) with no history of malignancy or other risk factors. Of these cases, 98.6% were rendered a Breast Imaging Reporting and Data System score of 4 on mammography before the CNB. Fifty-one cases (13.8%) were found to have microcalcifications on microscopic examination of CNB. A total of 7 (1.9%) of 370 cases were upgraded to invasive carcinoma, ductal carcinoma in situ, or pleomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
3
30
2
Order By: Relevance
“…Li et al 13 studied a population of similar ethnic composition (77% Caucasian, and 19.5% African American), and reported a 1.9% upgrade rate, similar to our study. In contrast, 70% of patients in the study of Rizzo et al were African American, and the upgrade rate was higher 6 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Li et al 13 studied a population of similar ethnic composition (77% Caucasian, and 19.5% African American), and reported a 1.9% upgrade rate, similar to our study. In contrast, 70% of patients in the study of Rizzo et al were African American, and the upgrade rate was higher 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Glenn et al 21 , however, described an upgrade rate of 4.7% in IDPs measuring <15 mm, but did not report radiologic-pathologic concordance. Other authors have shown that size by imaging is not predictive of upgrade 13,21 . In our study, the mean imaging size of lesions with and without upgrade was comparable (9.8±2.3 mm vs 9±0.5 mm, respectively).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies investigated which clinical and imaging features are predictive for an upgrade to carcinoma and suggested characteristics such as larger lesion size [7], presence of microcalcifications [14], older patient age [5], and palpable mass lesions [11]. However, to our knowledge, almost all of these previous studies focused on only a single imaging modality, and there is still no consensus as to which imaging features warrant surgical excision.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Others favor imaging follow-up in some or all biopsy-proven benign papillomas. [12][13][14][15] As a result, the management of suspected intraductal papillomas has become challenging.…”
mentioning
confidence: 99%